2006
DOI: 10.1111/j.1469-7998.2006.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Population spatial structuring on the feeding grounds in North Atlantic humpback whales (Megaptera novaeangliae)

Abstract: Population spatial structuring among North Atlantic humpback whales Megaptera novaeangliae on the summer feeding grounds was investigated using movement patterns of identified individuals. We analysed the results from an intensive 2-year ocean-basin-scale investigation resulting in 1658 individuals identified by natural markings and 751 individuals by genetic markers supplemented with data from a long-term collaborative study with 3063 individuals identified by natural markings. Re-sighting distances ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 41 publications
5
93
0
1
Order By: Relevance
“…In general, humpback whales appear to be good bioindicators, reflecting what is known about environmental levels of contaminants. This lends further support to studies of humpback whale population structure, which have shown strong site fidelity of whales to feeding areas [10][11][12][13]. For example, whales that feed off the coasts of California, Oregon, and Washington are thought to form a relatively distinct feeding aggregation [10].…”
Section: Geographic Variation Of Pops In Humpback Whalesmentioning
confidence: 61%
See 2 more Smart Citations
“…In general, humpback whales appear to be good bioindicators, reflecting what is known about environmental levels of contaminants. This lends further support to studies of humpback whale population structure, which have shown strong site fidelity of whales to feeding areas [10][11][12][13]. For example, whales that feed off the coasts of California, Oregon, and Washington are thought to form a relatively distinct feeding aggregation [10].…”
Section: Geographic Variation Of Pops In Humpback Whalesmentioning
confidence: 61%
“…Whales that overwinter in Central America were typically resighted in southern California feeding grounds, whereas those overwintering in mainland Mexico and Baja California were seen feeding primarily in northern California. Substructuring and fidelity of humpback whales to smaller areas within a feeding ground has also been observed in the North Atlantic [13]. Previous work examining PCB/DDE ratios in harbor porpoise (Phocoena phocoena) along the U.S. West Coast also found distinct regional patterns in contaminants [40].…”
Section: Geographic Variation Of Pops In Humpback Whalesmentioning
confidence: 82%
See 1 more Smart Citation
“…Instances of extreme long-distance movement may represent exploration of a new habitat or a navigational miscue, and the observation presented here could be explained by either of these plausible explanations. Humpback whales may make large longitudinal movements while feeding at high latitudes, especially in changeable or unpredictable circumstances [31,32]. Such movement may occur through tracking prey, exploring potential foraging sites or in the Southern Ocean through drift with the Antarctic Circumpolar Current.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating population trends for species that are widely dispersed, sometimes at the scales of whole ocean basins, is complicated and resource intensive (Forney, 2000;Taylor et al, 2007;Hammond, 2010), but can be facilitated when species exhibit predictable migrations to form seasonal breeding aggregations (Poncet et al, 2006;Stevick et al, 2006;Ramos et al, 2009;Foote et al, 2010). This is the case for marine turtles, where nonbreeding adults disperse at scales that range from regional to whole ocean basins .…”
Section: Introductionmentioning
confidence: 99%